2003
DOI: 10.1124/mol.64.6.1586
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor Isoform Expression Changes in Human Gestational Tissues with Labor at Term

Abstract: Peroxisome proliferator-activated receptors (PPARs) are a family of nuclear receptors that are involved in lipid metabolism, differentiation, proliferation, cell death, and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…In the present study, we found that the PPAR-␦ ligand GW501516 (1 M) was also active in inhibiting IL-1␤-induced PGE 2 production, suggesting that the high concentration effect of 15d-PGJ 2 in WISH cells may be mediated, at least in part, through the activation of PPAR-␦. We have recently published data that support this argument, showing that the PPAR-␥ antagonist GW9662 is only partially effective at inhibiting 15d-PGJ 2 -induced activation of PPRE-driven reporter in JEG3 cells, whereas it completely abolished the rosiglitazone effect (Berry et al, 2003). The inhibition of 15d-PGJ 2 effects observed with the PPAR dominant-negative construct further supports the conclusion that 15d-PGJ 2 mediates its anti-inflammatory activity through the activation of PPARs because the PPAR D/N construct inhibits the transcriptional activity of all three PPAR isoforms (Berger et al, 2000).…”
Section: Discussionsupporting
confidence: 48%
“…In the present study, we found that the PPAR-␦ ligand GW501516 (1 M) was also active in inhibiting IL-1␤-induced PGE 2 production, suggesting that the high concentration effect of 15d-PGJ 2 in WISH cells may be mediated, at least in part, through the activation of PPAR-␦. We have recently published data that support this argument, showing that the PPAR-␥ antagonist GW9662 is only partially effective at inhibiting 15d-PGJ 2 -induced activation of PPRE-driven reporter in JEG3 cells, whereas it completely abolished the rosiglitazone effect (Berry et al, 2003). The inhibition of 15d-PGJ 2 effects observed with the PPAR dominant-negative construct further supports the conclusion that 15d-PGJ 2 mediates its anti-inflammatory activity through the activation of PPARs because the PPAR D/N construct inhibits the transcriptional activity of all three PPAR isoforms (Berger et al, 2000).…”
Section: Discussionsupporting
confidence: 48%
“…PPARγ is expressed in the choriodecidual tissues [77], including decidual macrophages [78], where it was suggested to participate in the process of labor [79]. Recently, we reported that PPARγ activation (via rosiglitazone) attenuates the pro-inflammatory response at the maternal-fetal interface induced by a microbial product [78] or activation of invariant natural killer T cells [55].…”
Section: Resultsmentioning
confidence: 99%
“…PPAR , PPAR / and PPAR are also expressed in gestational tissues (in the amnion, choriodecidua, and placenta) (Berry et al 2003). PPAR / is strongly expressed during decidualization, and regulates embryo implantation (Lim & Dey 2000.…”
Section: Ppars -Mediators Of Endocrine Disruptors Of Environmental Ormentioning
confidence: 99%